PERANCANGAN INTERFACE APLIKASI INFORMASI RUANG KELAS KOSONG BERBASIS MOBILE DENGAN METODE USER-CENTERED DESIGN (UCD) - Okti Felina Angreini; Fitriah (Universitas Methodist Indonesia, 2025)
The rapid advancement of information technology in higher education necessitates greater efficiency in managing academic resources, including the provision of information on empty classrooms. Students and lecturers often encounter difficulties in locating available rooms due to manual processes and non–user-friendly interfaces. This study aims to design a web-based application interface for empty classroom information using the User-Centered Design (UCD) approach to enhance User Experience (UX). A qualitative research method was employed, incorporating observation and interviews with prospective users to understand their needs, expectations, and usage contexts. The design outcome is a prototype interface comprising the splash screen, login, main page, and user profile. The design emphasizes ease of navigation, clarity of information, and continuous user involvement throughout the design process. By implementing UCD, the application is expected to provide an effective solution for real-time discovery of empty classrooms.